2008
DOI: 10.1007/s10689-008-9206-8
|View full text |Cite
|
Sign up to set email alerts
|

Absence of founder BRCA1 and BRCA2 mutations in coetaneous malignant melanoma patients of Ashkenazi origin

Abstract: Our results suggest a limited role for the three Ashkenazi BRCA founder mutations in CMM risk among the Ashkenazi Jewish population. Therefore, screening patients with CMM for these BRCA1/2 mutations is not warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In 1999, the Breast Cancer Linkage Consortium reported a relative risk of 2.6 for melanoma among BRCA2 carriers, compared to the general population (95% CI: 1.3-5.2) [2]. However, a recent study from Israel failed to find a single carrier of an Ashkenazi founder mutation among 92 patients with melanoma, unselected for family history of cancer [46]. In 2007, Monerrat and colleagues reported on a series of 82 European patients with double primary breast cancer and melanoma, unselected for family history [47].…”
Section: Discussionmentioning
confidence: 99%
“…In 1999, the Breast Cancer Linkage Consortium reported a relative risk of 2.6 for melanoma among BRCA2 carriers, compared to the general population (95% CI: 1.3-5.2) [2]. However, a recent study from Israel failed to find a single carrier of an Ashkenazi founder mutation among 92 patients with melanoma, unselected for family history of cancer [46]. In 2007, Monerrat and colleagues reported on a series of 82 European patients with double primary breast cancer and melanoma, unselected for family history [47].…”
Section: Discussionmentioning
confidence: 99%
“…111 Additionally, one study reviewed the role of BRCA1 and BRCA2 in CMM patients and found that no mutation was present in any of the 92 familial melanoma cases. 112 Li et al 113 reported a significant association between APEX1 and CMM, with an OR of 0.59 (95% CI, 0.42-0.83), but another study by the same authors 114 failed to find an association for XPC.…”
Section: Dna Repairerelated Genesmentioning
confidence: 98%
“…Given that some studies [61] suggest an increased risk of melanoma in the presence of mutations in this gene, whereas others [62] have been unable to demonstrate this, no sound conclusions can be drawn regarding this gene. Other genes are also being investigated; genome-wide association studies [63–65] have identified several loci that may correlate with increased melanoma risk, but the biological mechanism of many of these has not yet been established.…”
Section: Cutaneous Melanomamentioning
confidence: 99%